2019
DOI: 10.3892/ijmm.2019.4374
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‑derived stem cells overexpressing SK4 calcium‑activated potassium channel generate biological pacemakers

Abstract: Recent studies have suggested that calcium-activated potassium channel (KCa) agonists increase the proportion of mouse embryonic stem cell-derived cardiomyocytes and promote the differentiation of pacemaker cells. In the present study, it was hypothesized that adipose-derived stem cells (ADSCs) can differentiate into pacemaker-like cells via over-expression of the SK4 gene. ADSCs were transduced with a recombinant adenovirus vector carrying the mouse SK4 gene, whereas the control group was transduced with GFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Taken together, those reports show a molecular involvement of KCa3.1 in cardiac and pacemaker fate through the activation of the ERK1/2 signaling pathway (Kleger et al, 2010;Yang et al, 2019). However, the channel expression itself and its role in the cardiac pacemaker mechanism were not mentioned.…”
Section: Expression and Role In The Heartmentioning
confidence: 94%
See 1 more Smart Citation
“…Taken together, those reports show a molecular involvement of KCa3.1 in cardiac and pacemaker fate through the activation of the ERK1/2 signaling pathway (Kleger et al, 2010;Yang et al, 2019). However, the channel expression itself and its role in the cardiac pacemaker mechanism were not mentioned.…”
Section: Expression and Role In The Heartmentioning
confidence: 94%
“…Recently, an independent group showed that rat adipocyte stem cells were effectively differentiated into pacemaker-like cells following SK4 adenoviral transduction. When those modified stem cells were injected in the heart, they generated an ectopic pacemaker after differentiation (Yang et al, 2019). An additional study focused on the dynamic gene expression in mouse AVN during development and reported a ninefold increase in SK4 transcripts (Horsthuis et al, 2009).…”
Section: Expression and Role In The Heartmentioning
confidence: 99%
“…This likely results in their inferior regenerative properties compared with ASCs [51]. Several studies with ASCs on their cardiac differentiation path described pacemaker derivation induced by transcription factor or channel protein genes [27,28,31,33,39,42].…”
Section: Introductionmentioning
confidence: 99%